The Stasi poetry circle: the creative writing class that tried to win the cold war - Oltermann, Philip (Faber & Faber, 2022)
Berlin, 1962. Morale is at rock bottom in East Germany, thrown into chaos by the new Berlin Wall. The Ministry for State Security is hunting for a new weapon in the war against capitalism - and their solution is stranger than fiction. Rather than guns, tanks, or bombs, the Stasi resolve to fight the enemy through rhyme and verse, winning the Culture Wars through poetry - and the result is the most bizarre book club in history. Consisting of 15 secret agents - from WW2 veterans to schoolboy recruits - the 'Working Group of Writing Chekists' met monthly from 1962 until the Wall fell. In a classroom adorned with portraits of Lenin, the spies wrote their own poetry and were taught verse, metre, and rhetoric by East German poet Uwe Berger. The regime hoped that poetry would sharpen the Stasi's 'party sword' by affirming the spies' belief in the words of Marx and Lenin, as well as strengthening the socialist faith of their comrades. But as the agents became steeped in poetry, revelling in its imaginative ambiguity, the result was the opposite. Rather than entrenching state ideology, they began to radically question it - and following a radical role reversal, the GDR's secret weapon dramatically backfired. Weaving unseen archival material with exclusive interviews from surviving members, Philip Oltermann reveals the incredible hidden story of a unique experiment: weaponising poetry for politics. Both a gripping true story and a parable about creativity in a surveillance state, this is The Lives of Others meets Dead Poets Society - and history writing at its finest.